2018
DOI: 10.1093/jas/sky379
|View full text |Cite
|
Sign up to set email alerts
|

Dietary deoxynivalenol and oral lipopolysaccharide challenge differently affect intestinal innate immune response and barrier function in broiler chickens1

Abstract: Dietary deoxynivalenol (DON) impairs the intestinal immune system and digestive functions of broiler chickens. However, little is known whether increasing doses of DON similarly affect the intestinal functions in different segments of the small intestine in chickens and whether a second oral challenge may potentiate those effects. The present objective was to investigate the effect of increasing dietary DON concentrations on the relative expression of genes for tight junction proteins, mucins, toll-like recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 48 publications
5
22
0
1
Order By: Relevance
“…The increase in total fecal mucin output with enteric ST inoculation agrees with a previous study that reported increased mucin secretion following immune stress in rats induced by live pathogenic E. coli [45]. Although there is some information indirectly relating the impact of immune stimulation on mucus secretion in pigs [53] and chickens [54], the present study demonstrates direct evidence that enteric Salmonella Typhimurium challenge increases mucus secretion. This contrasts the lack of fecal mucin output response in LPS challenged pigs reported here.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in total fecal mucin output with enteric ST inoculation agrees with a previous study that reported increased mucin secretion following immune stress in rats induced by live pathogenic E. coli [45]. Although there is some information indirectly relating the impact of immune stimulation on mucus secretion in pigs [53] and chickens [54], the present study demonstrates direct evidence that enteric Salmonella Typhimurium challenge increases mucus secretion. This contrasts the lack of fecal mucin output response in LPS challenged pigs reported here.…”
Section: Discussionsupporting
confidence: 92%
“…2 ). These results suggested that the addition of nontoxic-dose DON could enhance the inflammatory response induced by LPS in IPEC-J2 cells, which were similar with earlier research that LPS combined with DON could induce a certain up-regulation of the proinflammatory response in the duodenum of broiler chickens ( Lucke et al, 2018 ). The NLRP3 inflammasome, a member of innate immune receptor NLR family which execute cellular inflammation processes, is expressed in gut epithelial cells and plays an important role in intestinal inflammation and infectious enteritis ( Hirota et al, 2011 ; Zmora et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Lower relative abundance of Escherichia-shigella in the PPEO and PROB groups compared to PC was associated with the reduction of LPS biosynthesis, LPS biosynthesis proteins, and bacterial secretion system in PROB and PPEO groups compared to NC and PC as indicated by KEGG pathway. LPS induce mucosal immune responses (69); thus, such responses to the overgrowth of opportunistic bacteria due to the dysbiosis caused by NE challenge might have been attenuated by PROB and PPEO supplementation.…”
Section: Discussionmentioning
confidence: 99%